Desenvolvimento de um fluorímetro microcontrolado para determinação de clorofila a em águas superficiais - Guerreiro, Thiago Brito (2010)
In this work a portable fluorimeter was developed and used for determination of chlorophyll a in water samples. The instrument was constructed using the following components: a microcontroller (PIC18F4550), two LEDs as light source, a multichannel photodiode (TCS-230) as detector and a digital display. LEDs with maximum emission at 405 and 760 nm were used. The detector is equipped with three internal optical filters inside with maximum sensitivity at 480, 540 and 690 nm besides the possible use without the optical filter with high sensitivity in the visible spectral region with maximum sensitivity at 680 nm. The microcontroller works as central processing unit controlling all components of the instrument by a program previously recorded in its memory eliminating the need of a microcomputer. The fluorimeter was calibrated using standard solutions of fluorescein and rhodamine 6G in HCl 1.0 x 10-5 mol L-1 and performance was compared with a commercial spectrofluorimeter, and the results are in agreement at a confidence level of 95%. A linear response range for fluorescein was obtained between 0.5 and 100.0 x 10-6 mol L-1 and a correlation coefficient of 0.996 and for rhodamine 6G a linear response range between 0.2 and 10.0 x 10-6 mol L-1 was obtained and a correlation coefficient of 0.989. The fluorimeter was used for determination of chlorophyll a in water samples and blue algae culture medium. The results were compared with a spetrophotometric method and were in agreement at a confidence level of 95%. A linear range of between 2.5 and 1333.6 x 10-6 g L-1 for chlorophyll a was obtained with a correlation coefficient of 0.995. The concentration range attend the requirements of CONAMA resolution n° 357 that classifies the water quality covering the concentrations of 10.0, 30.0 and 60.0 x 10-6 g L-1 for different classes of water. The fluorimeter is inexpensive, easy to use shows, low power consumption allowing the feed with batteries, small size (10 cm x 20 cm x 15 cm) and with weight of 0.76 kg. The fluorimeter can be used to determine species with excitation at 405 and or 476 nm and emission across the visible range with excellent performance.